ANALYSIS OF THE EXISTING SYSTEM IN UKRAINE INDICATORS SECURITY BUDGET - Svitlana Onishchenko (European Cooperation, 2016)
In Ukraine solve extremely complex and responsible tasks related to the scale of global problems that are on the agenda and poses a risk to public safety Ukraine, hindering effective development of the national economy. The article contains methodical approaches evaluation of financial and budgetary security of Ukraine. The attention that the basis of financial stability of the state in the context of globalization is to improve the budget process and in forming an effective budget system from the standpoint of safety, while important place should be given to strengthening fiscal security. The dynamics of current trends and indicators of budget security. The main problem issues in public finance and public debt. The necessity of improving the methodological approach to determine the level of security on the basis of system threats and globalization processes.